Anti-Inflammatory Activity of a Cyclic Tetrapeptide in Mouse and Human Experimental Models - Michał Zimecki; Jolanta Artym; Wojciech Kałas; Leon Strządała; Katarzyna Kaleta-Kuratewicz; Jan Kuryszko; Andrzej Kaszuba; Krzysztof Kaczmarek; Janusz Zabrocki (MDPI AG, 2020)
A cyclic tetrapeptide Pro-Pro-Pheβ3ho-Phe (4B8M) was tested for immunosuppressive activity and potential therapeutic utility in several in vitro and in vivo mouse and human models. The tetrapeptide was less toxic for mouse splenocytes in comparison to cyclosporine A (CsA) and a parent cyclolinopeptide (CLA). The tetrapeptide demonstrated potent anti-inflammatory properties in antigen-specific skin inflammatory reactions to oxazolone and toluene diisocyanate as well to nonspecific irritants such as salicylic acid. It also inhibited inflammatory processes in an air pouch induced by carrageenan. In addition, 4B8M proved effective in amelioration of animal models corresponding to human diseases, such as nonspecific colon inflammation induced by dextran sulfate and allergic pleurisy induced by ovalbumin (OVA) in sensitized mice. The tetrapeptide lowered expression of EP1 and EP3 but not EP2 and EP4 prostaglandin E2 (PGE2) receptors on lipopolysaccharide-stimulated Jurkat T cells and ICAM-1 expression on human peripheral blood mononuclear cells (PBMC). Its anti-inflammatory property in the carrageenan reaction was blocked by EP3 and EP4 antagonists. In addition, 4B8M induced an intracellular level of PGE2 in a human KERTr keratinocyte cell line. In conclusion, 4B8M is a low toxic and effective inhibitor of inflammatory disorders with potential therapeutic use, affecting the metabolism of prostanoid family molecules.